Investigation on the early pressure load characteristics of bubbles in near-field underwater explosion with condensed-phase CL-20 explosive detonation - Yi Hao; Zhenxin Sheng; Bo Yan; Teng Xie; Lunping Zhang; Haibin Mao; Jun Yu (AIP Advances)
This study investigates the early pressure characteristics of CL-20 explosives in near-field underwater explosions, focusing on the second ultra-high-pressure pulse in the detonation product zone. We use a compressible multiphase fluid solver with high-order finite difference schemes, including fifth-order weighted essentially non-oscillatory for spatial and third-order total variation diminishing Runge–Kutta for temporal discretization. The level-set method and modified ghost fluid method accurately capture multiphase interface dynamics. Validation against 1D detonation wave tests confirms the accuracy of our burn model. Numerical simulations of cylindrical and spherical CL-20 charges under near-field conditions show good agreement with the experimental data, highlighting the model’s precision in predicting shock wave propagation and interface motion. In spherical charges, the second pulse arises from rarefaction wave reflections within the gaseous products. The analysis of peak pressures at various distance-to-radius ratios provides insights into pressure distribution. These findings demonstrate the effectiveness of our numerical model in simulating complex detonation phenomena, offering valuable insights for both theoretical and practical applications.